Do inhaled [beta]2-agonists have an ergogenic potential in non-asthmatic competitive athletes? - Kindermann, W. (Sports Medicine, 2007)
The prevalence of asthma is higher in elite athletes than in the general population. The risk of developing asthmatic symptoms is the highest in endurance athletes and swimmers. Asthma seems particularly widespread in winter-sport athletes such as cross-country skiers. Asthmatic athletes commonly use inhaled [beta]2-agonists to prevent and treat asthmatic symptoms. However, [beta]2-agonists are prohibited according to the Prohibited List of the World Anti-Doping Agency. An exception can be made only for the substances formoterol, salbutamol, salmeterol and terbutaline by inhalation, as long as a therapeutic use exemption has been applied for and granted. In this context, the question arises of whether [beta]2-agonists have ergogenic benefits justifying the prohibition of these substances.